Gender inequalities in the 21st century : new barriers and continuing constraints - Scott, Jacqueline (Edward Elgar CheltenhamGB, 2011)
Considers briefly the way that gender patterns in paid and unpaid work are changing across Europe and North America. Examines how the concept of gender alone is not sufficient for analysing inequalities, and crucially, other differences such as class, race, ethnicity and age modify people's employment and family experiences. Examines longer-term trends in gender equality, emphasises how much has been achieved in the struggle for greater equality over time, particularly in terms of the expansion of education and employment opportunities for women. Notes the distance there to go in achieving gender equality and the slow pace of change, particularly in terms of the shifts in the amount of caring and unpaid work that is undertaken by men.